Corpo a corpo (1970) de Oduvaldo Vianna Filho: do texto dramático à encenação do Grupo Tapa de São Paulo em 1995 - Araújo, Sandra Rodart (2006)
In the 1960s and 1970s aesthetic changes marked arts in Brazil, including drama, which we discuss by analyzing Corpo a corpo (1970), a play that conveyed those changes and that was written by Oduvaldo Vianna Filho, a man of drama and a Communist Party enthusiast who intended to deal with ideas of the so-called drama vanguard at the time. To begin with, we discuss the play but placing it at the time when it was produced. Then we discuss its performance by the theater group Grupo Tapa de São Paulo in 1995; in bringing this play up to date Grupo Tapa did the same to questions raised in the 1970s. Finally we try to understand how this play performed in 1971, 1975, and 1995 was received by the journalistic criticism. As critics leave signs of the historicity of their time in their analysis of the play, we try to understand how the scene brings a text from the past up to date and stimulates the discussion of current issues.